The impact of host plant species on instar duration and body weight of nymphal Lycorma delicatula - Kreitman, Devin; Keena, Melody A.; Nielsen, Anne L.; Hamilton, George (Frontiers in Insect Science, 2023)
The spotted lanternfly, Lycorma delicatula (White) (Hemiptera: Fulgoridae), is an invasive species of planthopper that was introduced to North America and is a threat to multiple industries. Nymphs and egg masses were collected to assess each instar’s rate of development at a constant temperature of 25°C on the following hosts: Ailanthus altissima (Miller) (Sapindales: Simaroubaceae), Vitis labrusca (L.) (Vitales: Vitaceae), Salix babylonica (L.) (Malpighiales: Salicaceae), Acer rubrum (L.) (Sapindales: Sapindaceae), Celastrus orbiculata (Thunberg) (Celastrales: Celastraceae), Ocimum basilicum (L.) (Lamiales: Lamiaceae), and Rosa multiflora (Thunberg) (Rosales: Rosaceae). Host plant species was found to have a significant effect on developmental time for nymphs in the first through third instars, as well as on nymphal survival. Nymphs failed to develop through the second instar on O. basilicum and the third and fourth instars on A. rubrum. Host plant species also had a significant effect on the mean weight of nymphs in the first, second, and fourth instars (but not in the third instar), and on the hind tibia length and forewing width of adult nymphs. This variability in L. delicatula developmental time by host plant species can potentially impact phenology models, which should be updated to reflect these new insights. Rearing practices should also be refined to account for host plant influences on the physiology of L. delicatula.